2003
DOI: 10.1093/carcin/24.3.453
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of lovastatin on mammary and prostate oncogenesis in transgenic mouse models

Abstract: The effects of lovastatin, a potent inhibitor of HMG CoA reductase, on experimental mammary and prostate oncogenesis, were studied in vitro and in vivo. Lovastatin inhibited cell growth in vitro in a dose-dependent manner for both mammary and prostate cancer cell lines, which was associated with p53-independent apoptosis. Flow cytometric analyses of lovastatin-treated mammary and prostate cancer cells demonstrated cell-cycle G(1) arrest, as well as decreases in S and G(2)/M fractions. p21(Waf1) and p27(Kip1) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
66
2
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 27 publications
3
66
2
1
Order By: Relevance
“…In general, various cancers are sensitive to statin treatment (33)(34)(35). Similarly, ovarian cancer cells may be sensitive to simvastatin treatment (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, various cancers are sensitive to statin treatment (33)(34)(35). Similarly, ovarian cancer cells may be sensitive to simvastatin treatment (12).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, statins induce apoptosis through both the extrinsic and intrinsic pathways. Shibata et al (34) reported that lovastatin induced p53-independent mitochondrial-mediated apoptosis in a mouse mammary carcinoma. The sensitivity of different cell types to statin-induced apoptosis varies; acute myeloid leukemic and neuroblastoma cells are more sensitive than acute lymphoblastic leukemic cells (40).…”
Section: Discussionmentioning
confidence: 99%
“…The indirect approach can be through the agents capable of inducing the expression of cyclin inhibitors or via peptides mimicking the effects of these inhibitors. In a number of studies, the indirect effect of cyclin inhibitor p21 has been demonstrated, either overexpression via viral and nonviral vectors (1)(2)(3)(4)(5)(6) or through the induction of p21 by different therapeutic agents (7)(8)(9)(10). We have demonstrated previously that anti-inflammatory/immunosuppressive drugs, e.g., cyclosporine (CsA) 2 , tacrolimus (TAC), and sirolimus (SRL) (11)(12)(13), induce the expression of cyclin inhibitor p21.…”
mentioning
confidence: 99%
“…Wu et al applied 5 μmol/L lovastatin to treat CHO cells for 32 hours and the proportion of cells in G1 phase was 90% (Wu and Gilbert, 2000). In addition, lovastatin at 10 and 20 μmol/L was applied to treat M6 cells and MCF-1 cells for 24 and 33 hours, respectively, and 78% and 77~96% of cells were identified to be in the G1 phase (Gupta et al, 2003;Shibata et al, 2003). Treatment of Pr14 cells and Pc-3M cells with 10 μmol/L lovastatin for 24 hours and 24~48 hours can achieve 82% and 68~90% of cells in G1 phase, respectively (Park et al, 2001;Shibata et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, lovastatin at 10 and 20 μmol/L was applied to treat M6 cells and MCF-1 cells for 24 and 33 hours, respectively, and 78% and 77~96% of cells were identified to be in the G1 phase (Gupta et al, 2003;Shibata et al, 2003). Treatment of Pr14 cells and Pc-3M cells with 10 μmol/L lovastatin for 24 hours and 24~48 hours can achieve 82% and 68~90% of cells in G1 phase, respectively (Park et al, 2001;Shibata et al, 2003). Treatment of T-24 cells with 30 μmol/L lovastatin may achieve 80% of cells in G1 phase and about 70~90% of Calu-1 cells were identified to be in the G1 phase following treatment with 30 μmol/L lovastatin (Jakobisiak et al, 1991;Vogt et al, 1997).…”
Section: Discussionmentioning
confidence: 99%